Sangam - Kapūra, Rāja, 1924-1988; Vyjayantimala, 1936-; Rajendra Kumar, 1929-1999; Pawar, Lalita, 1916-1998; Iftiqar (Shemaroo Video, 2001)
Story of a military officer who loses touch with his family and returns to find his wife in love with his friend.